Genomic, Physiologic, and Symbiotic Characterization of Serratia marcescens Strains Isolated from the Mosquito Anopheles stephensi - Chen, Shicheng; Blom, Jochen; Walker, Edward D. (Frontiers in Microbiology, 2017)
Strains of Serratia marcescens, originally isolated from the gut lumen of adult female Anopheles stephensi mosquitoes, established persistent infection at high rates in adult A. stephensi whether fed to larvae or in the sugar meal to adults. By contrast, the congener S. fonticola originating from Aedes triseriatus had lower infection in A. stephensi, suggesting co-adaptation of Serratia strains in different species of host mosquitoes. Coinfection at high infection rate in adult A. stephensi resulted after feeding S. marcescens and Elizabethkingia anophelis in the sugar meal, but when fed together to larvae, infection rates with E. anophelis were much higher than were S. marcescens in adult A. stephensi, suggesting a suppression effect of coinfection across life stages. A primary isolate of S. marcescens was resistant to all tested antibiotics, showed high survival in the mosquito gut, and produced alpha-hemolysins which contributed to lysis of erythrocytes ingested with the blood meal. Genomes of two primary isolates from A. stephensi, designated S. marcescens ano1 and ano2, were sequenced and compared to other Serratia symbionts associated with insects, nematodes and plants. S. marcescens ano1 and ano2 had predicted virulence factors possibly involved in attacking parasites and/or causing opportunistic infection in mosquito hosts. S. marcescens ano1 and ano2 possessed multiple mechanisms for antagonism against other microorganisms, including production of bacteriocins and multi-antibiotic resistance determinants. These genes contributing to potential anti-malaria activity including serralysins, hemolysins and chitinases are only found in some Serratia species. It is interesting that genome sequences in S. marcescens ano1 and ano2 are distinctly different from those in Serratia sp. Ag1 and Ag2 which were isolated from Anopheles gambiae. Compared to Serratia sp. Ag1 and Ag2, S. marcescens ano1 and ano2 have more rRNAs and many important genes involved in commensal and anti-parasite traits.